10.34 PHILOSOPHY AS A SOCIAL CONSCIOUSNESS - Salimov Bakhriddin Lutfullaevich. Associate Professor of TDTr.U. Jumaniyazova Nasiba Saparbaevna. Senior teacher of TDTr.U. Mavlonov Elnur Farrux o‘g‘li. Student of TDTr.U. (Innovative technologies in construction Scientific Journal, 2024)
In the article, the difference of philosophy from other forms of social consciousness is that it examines the world as a whole, studies the general characteristics of nature, shows the ways and methods of knowing the reasons for its development, human thinking and the general laws of society, and its contribution to changing the world. addition is analyzed. Keywords: Social consciousness, trait, theory, thinking, category and laws. What is the nature of philosophy as social consciousness? What problems has philosophy debated and continues to debate? What role does he play in society? How will it evolve as a specialty? There is no single answer and no single understanding of these issues. There are many philosophical theories, systems, directions and schools. The problems of philosophy, its nature, origin can be justified only when approached from the point of view of the conducted researches. The difference between philosophy and other forms of social consciousness is that it examines the universe as a whole. He studies the general characteristics of nature, shows the way and method of knowing the reasons for its development, human thinking and the general laws of society, and contributes to changing the world.